Analisis Dampak Ekspor Dan Investasi Dalam Meningkatkan Pertumbuhan Ekonomi Indonesia - Wiwit Setyo Wardani; Agus Wiastono (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2024)
The goal of this study is to determine how the trade sector influences the value of Indonesia’s exports to various destination nations. In this study, the author employs the literature research approach, which involves gathering research data and information from library sources such as books, research findings, and other reading. This research employed secondary data gathered from international trade statistics. Trade) Indonesian statistics with time series data features. Economic growth is a country’s main priority. International trade is one of two major variables influencing Indonesia’s economic growth. Countries will profit directly from international commerce by improving their national GDP and economic growth rate. The study plan for this topic is to employ descriptive research methodologies, specifically to describe the aim. In economics, international commerce is defined as exports and imports, and the flow of international trade in this study is the same as exports and imports to estimate the impact of exports and investment on Indonesian economic growth.